2009
DOI: 10.1007/s00445-009-0280-z
|View full text |Cite
|
Sign up to set email alerts
|

Volcanology and eruptive styles of Barren Island: an active mafic stratovolcano in the Andaman Sea, NE Indian Ocean

Abstract: Barren Island (India) is a relatively little studied, little known active volcano in the Andaman Sea, and the northernmost active volcano of the great Indonesian arc. The volcano is built of prehistoric (possibly late Pleistocene) lava flows (dominantly basalt and basaltic andesite, with minor andesite) intercalated with volcaniclastic deposits (tuff breccias, and ash beds deposited by pyroclastic falls and surges), which are exposed along a roughly circular caldera wall. There are indications of a complete ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 88 publications
2
58
0
1
Order By: Relevance
“…8b the surface of the proximal flow was 'torn' transverse to flow direction. Similar morphology was observed by Sheth et al (2009) in lavas on Barren Island (India), who considered their examples to represent a form of toothpaste lava. In the example shown in Fig.…”
Section: Late-stage 'Squeeze-up' Extrusionsmentioning
confidence: 59%
See 2 more Smart Citations
“…8b the surface of the proximal flow was 'torn' transverse to flow direction. Similar morphology was observed by Sheth et al (2009) in lavas on Barren Island (India), who considered their examples to represent a form of toothpaste lava. In the example shown in Fig.…”
Section: Late-stage 'Squeeze-up' Extrusionsmentioning
confidence: 59%
“…The name of the mechanism derives from the fact that progressive pressurisation of a flow lobe by an overlying unit is similar to the squeezing of toothpaste from a tube, and does not refer to the resultant extrusion, which may or may not be the toothpaste lava of Rowland and Walker (1987). Macdonald (1972), citing Nichols (1939), used the term 'squeeze-up' to describe surface features ranging from elongate bulbous ridges to sharp pointed wedges, resulting from upwelling though pāhoehoe lava crusts on Hawai'i (see also Rowland and Walker 1987;Hon et al 1994;Harris et al 2009;Sheth et al 2009). Such features have been described on Etnean slab-crusted flows by Guest and Stofan (2005), where they consist of toes or several metres long rolls of pāhoehoe-like lava.…”
Section: Late-stage 'Squeeze-up' Extrusionsmentioning
confidence: 96%
See 1 more Smart Citation
“…The volcano had historic eruptions during 1787-1832. After 159 years of dormancy it became active in 1991 and has remained active since then with almost continuous tephra eruptions and produced at least four major lava eruptions in 1991, 1995-1996, 2005-2006and 2009(Sheth et al 2009). Radiocarbon dating of marine sediments interlayered with ash in a core collected from the Andaman Sea, *32 km southeast of the volcano, revealed that the volcano had at least seven major tephra eruptions during the last 70 ka (Awasthi et al 2010).…”
Section: Volcanic Landformsmentioning
confidence: 98%
“…This initial study, coupled with field documentation of volcanic features and petrographic, mineralogical and geochemical analysis of the fragmental ejecta (lava and coarser pyroclastic debris), led to the publication of a pictorial monograph on Barren volcano (Shanker et al 2001). Sheth et al (2009) provided a praiseworthy description and documentation of features of the pre-historic volcanoes on Barren Island and established the pre-historic eruptive history. While petrological and geochemical studies of past and current eruptions (Alam et al 2004;Pal et al 2007aPal et al , 2010 have helped to constrain the origin and evolution of subsurface magma; however, poor documentation and incorrect interpretations of the active lava flows and identification of lavas of particular eruptions during the last two decades have left plenty of scope for re-examination and further work (see Chapter 12 for details), partly provided by Bandopadhyay et al (2014).…”
Section: Thematic Work and Resource Characterizationmentioning
confidence: 99%